Rapid Vapor-Phase Deposition of High-Mobility p-Type Buffer Layers on Perovskite Photovoltaics for Efficient Semitransparent Devices - Jagt, Robert A (American Chemical Society, 2020)
10.1021/acsenergylett.0c00763